Diet of Glossogobius callidus (Teleostei: Gobiidae) in freshwater impoundments in the Sundays River Valley of the Eastern Cape, South Africa. Issue 4 (6th December 2019) - Mofu, L; Woodford, DJ; Wasserman, RJ; Dalu, T; Weyl, OLF
Abstract : Despite the high abundance of the gobiid fish Glossogobius callidus in many freshwater ecosystems in South Africa, very few studies have assessed the biology and ecology of the species. Here, we investigated the diet of G. callidus populations sourced from Sundays River irrigation ponds. A total of 571 fish grouped into two size classes (TL, range ± SD: juveniles of 20–60 ± 45 mm; adults of 61–140 ± 85 mm) were sampled by seine netting; prey items were removed from the guts and identified and sorted to obtain dietary information for each prey group. Of the examined guts, 97% contained prey comprising 17 taxa within 10 taxonomic groups. Teleosts were identified to species level, whereas most dietary components were identified to a broad taxonomic group. Aquatic invertebrates were the most important component of the diet of G. callidus, but the index of relative importance (%IRI) of dominant invertebrate taxa varied according to ontogenetic stage of G. callidus and season. Prey taxa included: Diptera, Hemiptera, Trichoptera, Odonata, Cladocera, Copepoda, Hydracarina, Amphipoda, Mollusca and Teleostei. Dipteran prey taxa were consistently encountered in both size classes and across all seasons. G. callidus can therefore be regarded as a generalist invertivore.